Teachers' Responses to the Implementation of the Independent Curriculum in English Language Learning - Ira Maisarah; Muhamad Kenzo Akbar (UNIB Press, 2025)
A major pedagogical change has been established in SMPN 18 Bengkulu Tengah, an education institution categorized as independent change supporting an independent curriculum, letting schools choose and implement learning materials that are directly related to their needs and context. However, only seventh-grade teachers are currently utilizing the independent curriculum. This study examines the responses of a seventh-grade English teacher towards the Independent Curriculum implemented at the SMPN 18, a secondary school in Bengkulu Tengah, Indonesia. A qualitative approach was used along with descriptive analysis. In order to capture teachers' experiences, views, and challenges, it was necessary to conduct wide-ranging interviews with the teachers and carefully observe the classroom dynamics; especially for English language teaching. The findings indicate teachers' perspectives regarding the benefits and challenges of the new curriculum and strategies which they use for its effective implementation.